Pengaruh Persaingan Kerja terhadap Produktivitas Kerja dengan Kepuasan Kerja sebagai Variabel Intervening pada PDAM Tirtanadi Limau Manis - Rosa Arta Clarissa; T. Lyza Tahura (Economics and Digital Business Review, 2025)
This research was conducted at PDAM Tirtanadi Limau Mas, a regional government-owned company engaged in providing clean water for community needs. The purpose of the study is to determine the effect of work competition on employee productivity in carrying out tasks, which is mediated by job satisfaction. The population in this study consists of employees working at the company, totaling 129 people, and the research sample was taken using a census, resulting in a sample size of 129 respondents. The data sources used were primary data, and the data collection technique employed was a survey, specifically a questionnaire. The data analysis techniques used include classical assumption testing, hypothesis testing, and path analysis. Based on the results of the research conducted, it shows that work competition partially affects job satisfaction and employee work productivity, while job satisfaction significantly affects employee work productivity. Simultaneously, work competition and job satisfaction significantly affect employee work productivity. Job satisfaction mediates the influence of work competition on employee work productivity. There is a moderate correlation between work competition and job satisfaction with employee work productivity at PDAM Tirtanadi in carrying out tasks. Employee work productivity can be explained by work competition and employee job satisfaction by 34.7%, while the remaining 65.3% can be explained by other variables not studied.